Impact investing in South Africa: identifying the global and local forces shaping this emerging investment market - Luckscheiter, Jochen (Research of GSB, 2018)
Triggered by the negative economic and social consequences of the 2008/09 global financial crisis, critical questions about how financial markets operate and how they benefit society have received renewed attention. In response to these questions, new investment strategies whose objectives go beyond pure financial return have emerged. Impact investing, a concept which closely co-exists with investment strategies such as socially responsible investing and responsible investing, is the latest attempt to combine financial return with a contribution to the sustainable development of society. Although still in the early days of its development, impact investing is a maturing field to the extent that it has developed into a global phenomenon with an emerging global support structure. While impact investing still occupies a tiny niche in South Africa's investment market, there is, at least compared to other developing countries on the African continent, a large community of South African impact investors who are looking to invest locally and beyond. This research investigates how far the understanding and practice of impact investing in South Africa is influenced by global efforts to build the field and to what extent context specific factors are shaping the way in which it is currently evolving. In other words, how both global convergence and local divergence mechanisms interplay to form what is the South African impact investing market. The research findings suggest that while the international movement towards the standardisation of impact investing practices has reached South Africa, context specific factors such as, among others, the social, racial and political legacy of apartheid and the existence of a sophisticated financial system are central to the way in which the field is taking shape.